Biocultural salient birds: which biological and cultural factors define them? - Ortega-Álvarez, Rubén; Casas, Alejandro (Frontiers in Conservation Science, 2023)
People's interests and needs, as well as biological characteristics of species, determine human perception and interaction with biodiversity. Thus, both cultural and biological factors should be considered to understand biocultural salient species. We studied the cultural and biological traits that influence bird salience for an indigenous community in Mexico. Firstly, we used bird lists mentioned by local people to compute salient indexes for species. Then, we constructed seven cultural association categories to represent the local significance of birds (recreation, beliefs, environment, food, crop damage, economy, pets) and compiled biological information about species (color, size, vocal activity, detectability, abundance, daily activity pattern, habitat, residence status, taxonomic family). Finally, we determined the relations of cultural associations and biological traits with bird salience using hierarchical clusters. We observed a strong link between salient birds and human feeding, as these animals were locally recognized as food and threat to crops. Salient and non-salient birds were differentiated by their residence status and vocal activity, as local awareness was greater towards year-round resident and vocal species. Salience related the most with abundance, followed by color and detectability. Our study provides a route to identify cultural and biological factors influencing biocultural salience, which might prove useful for establishing conservation initiatives, public policies, and environmental education actions.